As representatividades designadas ao patrimônio cultural pela comunidade rural-urbana da Vila do Distrito de Guaragi, Ponta Grossa/PR - Grilo, Rubia Batini (2013)
This dissertation was prepared starting from the assumption that the historical and cultural heritage built as architectural representation, consists of meanings and symbols that express the identity and historical experiences of a people, while contributing to the maintenance of the social memory. With this parameter - considering the spatial area, the urban village of the district rural municipal Guaragi, Ponta Grossa/PR (with its particularities, peculiarities and context) - the research is considered relevant to verify and analyze which one(s) to representative(s) is(are) designated to shareholders as a means of demonstrating their importance in the collective social site. Thus, for this study of the representation related to heritage was investigated, it was decided by the State School Field Dr. Munhoz da Rocha, being the equity presented analysis conditions, whereas the other local heritage, the railway station, was being rebuilt. Thus, to achieve the central objective of this research was necessary theoretical subjects about the issues involving the proposed discussion and use qualitative methodology, which helped to know that, through the acquisition of graphic representations (drawings) and the questionnaires, the significant elements that are part of the experience of local residents. From this, we sought to identify and analyze the factors affecting the reality experienced by local residents, i.e., the geographical context in relation exists in rural and urban spatial area (the village) and the historical-economical and socio-cultural factors that led the current reality. Then research turned understanding of cultural heritage, its historical construction and legislation established national forums, regional and local level as a way to support the understanding, and then analyze the data acquired from the field research, to be presented at the time that the research examines how the residents were related to the existing cultural heritage, which ones have the notion, which ones tied meanings and importance, starting with the abstract framework coming to a close and with the object that collaborated with the research, the school in question. The survey results showed that for the local population cultural heritage is linked to economic factors, through tourism, politics, the possibility of investment of rulers, historical, through the consecration of local history and memory, which ones confirms the story and makes links of symbolic significance to the local society with cultural heritage. Also found through the search result that other buildings have heritage conditions. That the rural/urban village existing in the same district gives a particular and new possibility of discussion concerning areas such as rural districts.